Factors Associated With Unhealthy Weight Control Behaviors Among a Representative Sample of U.S. High School Students. (December 2022) - Weng, Chung-Bang; Sheu, Jiunn-Jye; Chen, Huey-Shys
Adolescents often practice unhealthy behaviors to lose weight or keep from gaining weight. Centers for Disease Control and Prevention has conducted biennial Youth Risk Behavior Survey (YRBS) of various health risk behaviors since 1991 using U.S. representative samples of high school students and is therefore best for us to identify risk/preventive factors associated with unhealthy weight control behaviors (UWCB). We quantitatively assessed the association between various health risk behaviors with UWCB by gender using YRBS data. Due to the absence of UWCB items since 2015, we analyzed the latest (2013) data using binary multiple logistic regression. Among the 13, 583 participants, 22.7% of girls and 10.1% of boys engaged in UWCB. Among girls and boys separately, the common significant factors included suicidal behaviors, alcohol drinking, misused prescription drug, feeling depressed, skipping breakfast, and attending physical education class. School nurses are suggested to have knowledge about the aforementioned risk factors and provide assessment, consultation, and education to help reduce UWCB.